1993
DOI: 10.1007/bf00710291
|View full text |Cite
|
Sign up to set email alerts
|

Residual adenylosuccinase activities in fibroblasts of adenylosuccinase‐deficient children: Parallel deficiency with adenylosuccinate and succinyl‐AICAR in profoundly retarded patients and non‐parallel deficiency in a mildly retarded girl

Abstract: Adenylosuccinase (ASase) catalyses both the conversion of succinyl-aminoimidazole carboxamide ribotide (succinyl-AICAR) into AICAR and that of adenylosuccinate into AMP in the synthesis of purine nucleotides. Its deficiency results in the accumulation in body fluids of the nucleosides corresponding to both substrates, succinyl-AICAriboside and succinyladenosine. Two main subtypes of the defect are type I with severe mental retardation and succinyladenosine/succinyl-AICAriboside ratios around 1, and type II wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…Assuming that there is equal expression and stability of the two mutant enzymes in the proband (unlikely given the decreased stability of the mutant enzymes), the residual activity in the proband would be ϳ30%. This is similar to the residual ASL activity found in many ASL patients (8,9,26).…”
Section: Subtilis Adenylosuccinate Lyasessupporting
confidence: 86%
“…Assuming that there is equal expression and stability of the two mutant enzymes in the proband (unlikely given the decreased stability of the mutant enzymes), the residual activity in the proband would be ϳ30%. This is similar to the residual ASL activity found in many ASL patients (8,9,26).…”
Section: Subtilis Adenylosuccinate Lyasessupporting
confidence: 86%
“…This result well supported the above substrate accumulation hypothesis for explaining the Type II essentiality of ADE13. ADE13 catalyzes two reactions with S-AMP and SAICAR as substrates, respectively (Van den Bergh et al 1993). It is unclear which one is responsible for the lethality of ADE13 deletion.…”
Section: Mechanisms Underlying the Type II Essentialitymentioning
confidence: 99%
“…Interestingly, the latter patient was heterozygous for mutation R190Q, which has also been identified heterozygously in two Czech siblings with moderately delayed development . Current evidence indicates that the more severe clinical presentations of ADSL deficiency are associated with S-Ado/ SAICA-riboside ratios around 1 in body fluids [Jaeken et al, 1988;Krijt et al, 1995;Maaswinkel-Mooij et al, 1997;Köhler et al, 1999], and with parallel loss of both ADSL activities [ Van den Bergh et al, 1991. The first mutation reported in ADSL deficiency, S438P, previously labelled S413P [Stone et al, 1992], was identified in two such profoundly affected siblings.…”
Section: Discussionmentioning
confidence: 98%
“…ADSL deficiency was diagnosed on the basis of positive Bratton-Marshall tests [Laikind et al, 1986] and confirmed by high-performance liquid chromatography (HPLC) analysis of cerebrospinal fluid (CSF) and/or urine [Jaeken and Van den Berghe, 1984;Simmonds et al, 1991]. In some patients, the diagnosis was corroborated by assay of ADSL in tissue samples [Jaeken and Van den Berghe, 1984;Van den Bergh et al, 1991]. Psychomotor retardation was profound in eight patients, intermediate in one , and mild in another [patient 8 in Jaeken et al, 1988].…”
Section: Subjectsmentioning
confidence: 99%